IMPROVING EMPLOYEE PERFORMANCE THROUGH COMPETENCE AND WORK DISCIPLINE : A CASE STUDY AT THE REGIONAL SECRETARIAT OFFICE OF PATI REGENCY - Suparmi, Suparmi; Nurchayati, Nurchayati; Juniarto, Galuh; Suprapti, Sri (LPPM STIE Muhammadiah Bandung, 2024)
This study aims to determine employee performance strategies through competence and work discipline. The population and sample used were employees of the Regional Secretariat Office of Pati Regency in the general section, totaling 50 respondents. The data collected were 50 respondents from the Regional Secretariat Office of Pati Regency, specifically the general section. The sampling technique used is a saturated sample. Data collection methods using primary data. The analysis technique used is multiple linear regression analysis, the results of the analysis reveal that partial competence can be used as a strategy to improve employee performance through knowledge, skills, experience, attitudes, and education levels that support the positive and significant results of the analysis, as well as work discipline that to improve employee performance can use work discipline through high attendance, obeying the rules, obeying work standards, working ethically according to the results of the analysis which show positive and significant.